Analysis of saving behavior in students of the faculty of economics and business at Malikussaleh University - Alda, Eva; Ristati, Ristati; Nurlela, Nurlela; Asbar, Yuli (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
This study aims to determine the saving behavior of students from the Faculty of Economics and Business at Malikussaleh University who come from outside the Aceh region. This study uses primary data using a research instrument in the form of a questionnaire with a sample of 100 respondents. The results of this study indicate the research instrument testing, for Validity, rcount > rtable (0.196) and Reliability, Cronchbach Aplha > Constant (0.6). The data analysis method used is multiple linear regression analysis and hypothesis testing in the form of a (partial) t-test. The results showed that financial literacy, parental socialization and self-control had a positive and significant effect on saving behavior, while peers had a negative and significant effect on saving behavior.